Examination of the stress and social phobia levels of 13-18 age group students participating in tennis training: tennis, social phobia, stress - Yigiter, Korkmaz; Koroglu, Mihrac (Progress in Nutrition, 2022)
The aim of this study is to examine the stress and social phobia levels of 13-18 age group students receiving tennis training in terms of some variables. In this study, the relational survey model, which is one of the quantitative research designs, was used. Stress level scale and social phobia scale were used as data collection tools in the research. These questionnaires were applied to students aged 13-18 attending tennis clubs in Sakarya. The data obtained from the students were transferred to the SPSS program and descriptive statistics were applied to indicate their demographic characteristics. Mann Whitney U test and Kruskal Wallis test were used to see if there is a significant difference between stress and social phobia points of students according to age, gender, and education level. A correlation test was applied to look at the relationship between stress and social phobia levels. As a result of the study, there was no significant difference in the stress and social phobia levels of tennis players attending tennis clubs in Sakarya in terms of age, gender, and class levels (p>0,05). In addition, there was no significant relationship between the stress and social phobia levels of tennis players (p>0,05).